2016
DOI: 10.2527/jas.2016-0505
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of energy, amino acids, and phosphorus in a novel source of soy protein concentrate and in soybean meal fed to growing pigs

Abstract: Three experiments were conducted to determine standardized ileal digestibility (SID) of CP and AA, DE and ME, and apparent total tract digestibility (ATTD) and standardized total tract digestibility (STTD) of P in a new source of soy protein concentrate (SPC) and in soybean meal (SBM). In Exp. 1, 9 barrows (initial BW: 13.08 ± 1.98 kg) were prepared with a T-cannula in the distal ileum and allotted to a triplicated 3 × 3 Latin square design with 3 diets and 3 periods. A nitrogen-free diet and 2 diets that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…The ATTD and STTD of P in corn fed to pigs obtained in this experiment are within the range reported by previous studies [ 3 , 7 , 11 , 13 , 19 ]. The ATTD and STTD of P in SBM are also in accordance with some previous reports [ 10 , 14 , 21 , 23 ], but are greater than values reported by Almaguer et al [ 6 ]. The difference may be explained by the different processes used for producing SBM in feed industry, during which the amount of hulls removed prior to oil extraction varies.…”
Section: Discussionsupporting
confidence: 92%
“…The ATTD and STTD of P in corn fed to pigs obtained in this experiment are within the range reported by previous studies [ 3 , 7 , 11 , 13 , 19 ]. The ATTD and STTD of P in SBM are also in accordance with some previous reports [ 10 , 14 , 21 , 23 ], but are greater than values reported by Almaguer et al [ 6 ]. The difference may be explained by the different processes used for producing SBM in feed industry, during which the amount of hulls removed prior to oil extraction varies.…”
Section: Discussionsupporting
confidence: 92%
“…However, although the DE (3,928 kcal/kg DM) and ME (3,875 kcal/kg DM) concentrations in corn were greater ( P < 0.01) than in FVW (DE = 2,570 kcal/kg DM; ME = 2,460 kcal/kg DM), this source of FVW had greater ME content than soybean hulls (2,139 kcal/kg DM) as reported by NRC (2012) . The concentrations of DE and ME in corn obtained in this experiment were similar to those reported in other studies ( NRC, 2012 ; Rojas and Stein, 2013 ; Oliveira and Stein, 2016 ). The relatively high DE and ME content in FW and SMW were likely due to the greater concentration of CP and EE in these two food waste sources compared with corn and FVW.…”
Section: Resultssupporting
confidence: 90%
“…This may be explained by the potential biosynthesis of these dispensable AA from other AA in the enterocytes to produce mucin, which contributes to an increase in endogenous Gly and Pro losses when compared with other AA ( Holmes et al, 1974 ; Reis de Souza et al, 2013 ). Other studies have reported similar losses of AA when high-fiber ingredients were fed to pigs to those observed in this study ( Almeida et al, 2011 ; Reis de Souza et al, 2013 ; Oliveira and Stein, 2016 ).…”
Section: Resultssupporting
confidence: 86%
“…The differences in results between fish meal and soybean meal is assumably due to the presence of phytate component such as oligosaccharide and anti-trypsin in soybean meal. The inferior results found for soybean meal was seemingly attributable to the presence of phytate compound (Banaszkiewicz, 2011;Tahir et al, 2012), non-protein soluble component such as oligosaccharide (Kocher et al, 2002;Oliveira and Stein, 2016), and trypsin inhibitor (Banaszkiewicz, 2011;Pacheco et al, 2013). Phytate compound in soybean meal has been reported to be varied with the range of betwen 1 and 1.5% (Banaszkiewicz, 2012).…”
Section: Resultsmentioning
confidence: 99%